2016
DOI: 10.1016/j.jcma.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Income-related health inequality of migrant workers in China and its decomposition: An analysis based on the 2012 China Labor-force Dynamics Survey data

Abstract: It is generally known that there is an unequal socioeconomic distribution of migrant worker health in China. In order to reduce the health inequality, the government should make a substantial effort to strengthen policy implementation in improving the income distribution for vulnerable groups. After this investigation, it is apparent that the findings we have made warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
6
36
2
Order By: Relevance
“…Numerous variables are available in CHARLS. Followed by prior empirical investigations [22][23][24][25][26][27], all possible variables that may produce migrants' health were considered in our study. Four groups of variables were considered in this study.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous variables are available in CHARLS. Followed by prior empirical investigations [22][23][24][25][26][27], all possible variables that may produce migrants' health were considered in our study. Four groups of variables were considered in this study.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Hong et al [13] examined health inequalities of older rural-to-urban migrant workers (aged 45-70) in three cities of China and found that the richer were at a disadvantage in health disparities. Wu et al [2] compared older rural-to-urban migrant workers (aged 50 and above) with the middle-aged rural-to-urban migrant workers (aged [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and young rural-to-urban migrant workers (aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and reported that older rural-to-urban migrant workers' mental health was inferior to that of middle-aged rural-to-urban migrant workers and young rural-to-urban migrant workers. However, Hong and Wu did not compare the health status with rural counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The health status and healthcare utilisation among internal migrants, a population defined as those who live in a new residence for more than 1 month but do not have a local ‘Hukou’ of the new residence (registered resident certificate), has become an important research focus in China. 1–5 The reason for this special interest is that within China’s three-tiered healthcare delivery system, there has been a tendency for people to pursue higher-level hospitalisation service, with admissions to tertiary hospitals increasing by 13.5 percentage points (from 22.5% to 36.0%) and admissions to primary care facilities decreasing from 38.4% to 26.4% between 2009 and 2015. 6 This tendency was more marked in internal migrants; 43.6% of migrants with admission chose the tertiary hospitals in 2014, higher by 7.6 percentage points than that in general population.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposing socioeconomic-related health inequality can help to uncover specific factors that are potentially modifiable by policy decision makers. The dominant decomposition approach, the Wagstaff decomposition method, was proposed by Wagstaff et al [22] and has been used extensively in previous studies [9, 23]. However, there are potential concerns with this decomposition method.…”
Section: Introductionmentioning
confidence: 99%